Answer :

Let Sn denotes the sum of first n terms of an AP.


Sum of first n terms = Sn = 4n2 + 2n


Then nth term is given by: an = Sn - Sn - 1


an = (4n2 + 2n) - [4(n - 1)2 + 2(n - 1)]


= (4n2 + 2n) - [4(n2 + 1 - 2n) + 2n - 2]


= 4n2 + 2n - 4n2 - 4 + 8n - 2n + 2


= 8n - 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Arithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses